Kemampuan Pemecahan Masalah Matematis Siswa Kelas X Ditinjau dari Self-Regulated Learning pada Model Creative Problem Solving Berbantuan Aplikasi Cymath - Aulia, Nurul Fajriyah Rizqi; Sari, Virgania (Papanda, 2026)
Mathematical problem-solving skills are important in mathematics learning, but these skills have not been optimally developed in 10th grade students at SMK Negeri 3 Semarang. One factor that is thought to play a role is Self-Regulated Learning. In addition, the application of appropriate learning models and media is needed, one of which is through the Creative Problem Solving model assisted by the Cymath application. This study aims to: (1) determine the difference in mathematical problem-solving skills between students who participate in Creative Problem Solving learning assisted by the Cymath application and direct learning; (2) to determine the effect of Self-Regulated Learning on students' mathematical problem-solving skills in Creative Problem Solving learning assisted by the Cymath application; and (3) to describe students' mathematical problem-solving skills in terms of Self-Regulated Learning. The research method used is a mixed method with a sequential explanatory design. The research population consisted of 10th grade students at SMK Negeri 3 Semarang in the 2025/2026 academic year, with subjects selected using purposive sampling techniques. Data analysis included testing the validity of research tools and instruments, quantitative data analysis in the form of normality tests, homogeneity tests, two-mean difference tests, and simple linear regression tests, as well as qualitative data analysis covering data validity, data reduction, data presentation, and conclusion drawing. The results showed that there was a difference in mathematical problem-solving abilities between students who participated in Creative Problem Solving learning assisted by the Cymath application and students who participated in direct learning. In addition, Self-Regulated Learning had an effect on students' mathematical problem-solving abilities. Students with high Self-Regulated Learning were able to meet all problem-solving indicators, students with moderate Self-Regulated Learning were not yet able to recheck the results, while students with low Self-Regulated Learning were not yet able to plan, implement, and recheck problem solving.